A select review reporting the quality of studies measuring endothelial dysfunction in randomised diet intervention trials. Issue 1 (14th January 2015) - Costello, Rebecca B.; Lentino, Cynthia V.; Saldanha, Leila; Engler, Marguerite M.; Engler, Mary B.; Srinivas, Pothur; Sempos, Christopher T.
<x content-type="archive" xml:space="preserve">Abstract</x> A quality assessment of the primary studies reported in the literature carried out using select dietary ingredients (DI) purported to affect vascular endothelial function was conducted through a systematic PubMed search from January 2000 to August 2012. A total of seventy randomised controlled trials with defined DI (folic acid (fifteen), n-3 fatty acids (twenty), cocoa (fifteen) and isoflavones (twenty)) and standardised measures of vascular endothelial function were evaluated. Jadad scores, quality scoring parameters for DI and flow-mediated dilation (FMD) methodology used were ascertained. A total of 3959 randomised subjects, mean age 51 (se 0·21) years (range 9–79 years), were represented in the dataset. The mean Jadad scores did not differ statistically among the DI studies, with the majority of the studies being of good quality. Higher DI quality scores were achieved by studies using the botanical ingredients cocoa and isoflavones than by those using the nutrient ingredients folic acid and n-3 fatty acids. The mean DI quality scores were 4·13 (se 0·34), 5·20 (se 0·47), 6·13 (se 0·41) and 6·00 (se 0·59) for the folic acid, n-3 fatty acid, cocoa and isoflavone intervention studies, respectively (and significantly different). The mean Corretti FMD scores were 7·27 (se 0·56), 7·46 (se 0·79), 6·29 (se 0·61) and 7·11 (se 0·56) for the folic acid, n-3 fatty acid, cocoa and isoflavone intervention studies, respectively (NS). FMD studies failed to adequately describe the equipment used and more than half failed to provide an adequate description of the procedures used for vascular image acquisition and measurement. DI can be utilised for dietary intervention studies; however, the methodology should be clearly reported using the guidelines for assessment for both DI and FMD.